2020
DOI: 10.1002/adma.202000575
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Carbonate‐Free Lithium|Garnet Interface Enabled by a Trace Amount of Sodium

Abstract: Garnet‐type solid‐state electrolytes (SSEs) are promising for the realization of next‐generation high‐energy‐density Li metal batteries. However, a critical issue associated with the garnet electrolytes is the poor physical contact between the Li anode and the garnet SSE and the resultant high interfacial resistance. Here, it is reported that the Li|garnet interface challenge can be addressed by using Li metal doped with 0.5 wt% Na (denoted as Li*) and melt‐casting the Li* onto the garnet SSE surface. A mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…The more intriguing results were observed in the "Li-Na" alloy case, which were published separately by Fu et al and Zhang et al at about the same time (Figure 7 (C,D)). 115,116 In both studies, it was observed that the addition of Na metal into molten Li depressed the contact angle and the interface ASR substantially. Nonetheless, the microstructures of the Li-Na molten mixtures are quite different because of the level of Na added.…”
Section: Intermetallic Interphases In Ssbsmentioning
confidence: 93%
“…The more intriguing results were observed in the "Li-Na" alloy case, which were published separately by Fu et al and Zhang et al at about the same time (Figure 7 (C,D)). 115,116 In both studies, it was observed that the addition of Na metal into molten Li depressed the contact angle and the interface ASR substantially. Nonetheless, the microstructures of the Li-Na molten mixtures are quite different because of the level of Na added.…”
Section: Intermetallic Interphases In Ssbsmentioning
confidence: 93%
“…Most of the garnet‐typed electrolytes are unstable in moisture, forming Li‐ion insulating hydroxides and carbonates (such as Li 2 CO 3 ) on their surfaces, thereby increasing the interfacial resistance 90 . Therefore, Li 2 CO 3 prevention and removal is the key point to improve the interface properties between garnet‐typed SSEs with electrodes.…”
Section: Methods To Solve Interfacial Problemsmentioning
confidence: 99%
“…carbonates (such as Li 2 CO 3 ) on their surfaces, thereby increasing the interfacial resistance. 90 Therefore, Li 2 CO 3 prevention and removal is the key point to improve the interface properties between garnet-typed SSEs with electrodes. By controlling the grain size of LLZO particles, the surface sensitivity towards moisture and CO 2 can be optimized.…”
Section: Garnet/cathode Interfacementioning
confidence: 99%
“…The LLZTO pellets (12 mm in diameter, 1 mm in thickness) and LLZTO particles ( D 50 = 200–400 nm) were synthesized via solid-state reactions as reported previously . The obtained LLZTO ceramics have a relative density of 99.6%.…”
Section: Methodsmentioning
confidence: 99%
“…Solid-state lithium-metal batteries (SSLMBs) have drawn broad attention owing to their potential high energy densities and improved safety. Solid-state electrolytes (SSEs) play critical roles in the performance of SSLMBs. , Among all of the SSEs, garnet-type oxide (e.g., Li 7 La 3 Zr 2 O 12 , LLZO) or its derivatives (e.g., Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , LLZTO) is a promising candidate owing to its high Li + conductivity at 25 °C, , wide electrochemical stability window and high chemical stability against Li anode. , Despite these merits, the development of LLZO-based SSLMBs is hampered by poor physical contact at the electrode/SSE interface, heterogeneous deposition of Li, and growth of Li dendrites from the anode. Numerous strategies such as Li-alloy electrodes, interlayers between Li and SSEs, Li hosts in the anode, lithiated graphite, and Li-metal ink are explored to reduce Li nucleation barrier through changing the lithiophobic Li/SSE interface to lithiophilic one. , Among the strategies based on Li-alloy electrodes, most alloy electrodes such as LiAl, , LiIn, LiSn, , and LiSi , suffer from pulverization due to alloying/dealloying reactions between Li and Al, In, Sn, and Si, thus limiting the cycle lifetime of LMBs. Recently, there are several reports of using metal such as Cu, which is chemically inert with Li, to be the Li host.…”
Section: Introductionmentioning
confidence: 99%